Peranan Influencer Game Valorant Terhadap Minat Beli dan Keputusan Pembelian Produk Valorant di Komunitas Valorant Indonesia - Hasibuan, Rayhan (Business Preneur: Jurnal Ilmu Administrasi Bisnis, 2024)
Online gaming has shown significant and promising growth. One example of an online game is Valorant. Valorant is experiencing a rapid increase in new players and active players, according to reports from August 2022, where there was an average of 21 million players in March, with 1.5 million players active daily. Additionally, there has been an increase in Content Creation aspects, such as the number of influencers and revenue. Based on this phenomenon, many Valorant Game Influencers provide reviews and recommendations for Valorant Game products. In a study titled "The Role of Valorant Game Influencers on Purchase Interest and Decision in the Valorant Community in Indonesia," researchers aim to investigate the role of Valorant Game Influencers on purchase interest and decision-making among the Valorant community and players in Indonesia. The methodology employed by the researcher in this study is descriptive and verificative. Surveys were used to collect data, which was then processed and analyzed using Structural Equation Modeling with the Partial Least Square method. The results of the analysis indicate that Influencers play a significant role in purchase interest but do not have a major impact on purchase decisions. Moreover, purchase interest has a significant influence on purchase decisions